PENETAPAN WALI ANAK HASIL PERNIKAHAN PEREMPUAN HAMIL DI LUAR NIKAH (STUDI KASUS DI KANTOR URUSAN AGAMA (KUA) KECAMATAN PALASA KABUPATEN PARIGI MOUTONG) - Lamatande, Rahli (Pusat Studi Gender dan Anak, IAIN Palu, 2020)
This study is regarding the Legalization of the Guardianship of Children Born Out of Wedlock (Case Study in Religious Affairs Office (KUA) of Palasa Subdistrict, Parigi Moutong District. Hence, the explanation is based on the problems of (1) What is the guardianship procedure of children born out of wedlock (case study in Religious Affairs Office (KUA) of Palasa Subdistrict, Parigi Moutong District)?, (2) What is the legal framework of guardianship of children born out of wedlock (case study in Religious Affairs Office (KUA) Palasa Subdistrict, Parigi Moutong District)?. This research used qualitative research method through observation and in-depth interview as well as documentation study. The data obtained were analyzed through data reduction technique, data presentation, data verification, and conclusion. The results of the study show that: (1). The guardianship procedures of children born from marriage in Religious Affairs Office of Palasa Subdistrict are put through in accordance with the procedures of general marriage. The first step was by registering the date of the marriage covenant with ten days grace period, completing the requirement, i.e., in N1 form, and so on. The family guardian of children born out of wedlock could be held if it meets the marriage requirements even though the parents committed adultery. After the requirements of religion and the national principles are fulfilled, nothing could hinder the biological father from becoming the family guardian in the marriage of daughter born out of wedlock. (2). The legal framework of guardianship of the children born out of wedlock in Religious Affairs Office (KUA) of Palasa Subdistrict is based on the regulation of Law Number 1 of 1974 on marriage, the Compilation of Islamic Law (KHI) article 99 and 103.